EKSISTENSI MASYARAKAT ADAT DALAM MEMPERTAHANKAN HAK ATAS TANAH ULAYAT (STUDI MASYARAKAT ADAT KEBATINAN MUARA SAKAL KABUPATEN PELALAWAN) - Wismar . Harianto (Universitas Islam Negeri sultan syarif kasim Riau, 2021)
Abstract This study aims to identify, study and analyze the existence of the Muara Sakal traditional community in defending their customary rights over their customary law communities' lands. Where the adat community of Muara Sakal kebatinan has a large area of ulayat land which did not escape the